1998
DOI: 10.1046/j.1365-2141.1998.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse immunostaining pattern for synthesized versus endocytosed alpha‐granule proteins in human bone marrow megakaryocytes

Abstract: Summary. The time of appearance and pattern of expression of several a-granule proteins, von Willebrand factor (VWF), fibrinogen and immunoglobulins (Ig) were examined and compared in human bone marrow megakaryocytes (MK) using an immunocytochemical approach. VWF is synthesized by immature MK, whereas it has been shown that fibrinogen is incorporated from the plasma into a-granules. The present study was undertaken in order to determine whether there are chronological and morphological differences in the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Platelet secretory granule protein cargo is synthesized in the MK ER and transported via vesicles derived from the trans-Golgi network 31 to early MVBs, which according to current models also receive cargo in endocytic vesicles as they mature and give rise to platelet lysosomes and α and dense 32 granules. 31, 33, 34 Transferrin receptor (TFR; CD71) undergoes clathrin-mediated endocytosis and is frequently used as marker of the MK recycling endocytic compartment, 35 while TGN46 is a marker of the trans-Golgi network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet secretory granule protein cargo is synthesized in the MK ER and transported via vesicles derived from the trans-Golgi network 31 to early MVBs, which according to current models also receive cargo in endocytic vesicles as they mature and give rise to platelet lysosomes and α and dense 32 granules. 31, 33, 34 Transferrin receptor (TFR; CD71) undergoes clathrin-mediated endocytosis and is frequently used as marker of the MK recycling endocytic compartment, 35 while TGN46 is a marker of the trans-Golgi network.…”
Section: Resultsmentioning
confidence: 99%
“…31, 33, 34 Transferrin receptor (TFR; CD71) undergoes clathrin-mediated endocytosis and is frequently used as marker of the MK recycling endocytic compartment, 35 while TGN46 is a marker of the trans-Golgi network. IFM examination of thiol isomerase expression in human MKs in serum-free culture revealed little overlap between ERp57, TFR and TGN46 (Figure 2 A; Video 5) or between PDI and the α-granule cargo proteins VWF (Figure S1A; Video 6) and thrombospondin-1 (TSP-1; not shown).…”
Section: Resultsmentioning
confidence: 99%
“…22 In vivo studies have recently confirmed these data. 25 vWF appears early also during MK maturation and is stored in a specific compartment at one pole of the ␣-granules. 3 In gray platelets, this polar distribution of vWF within ␣-granules is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen and lung biopsies were withdrawn and embedded in paraffin. Four-m sections were cut and left for 24 hours at 37 Њ C. After deparaffinization and rehydration, immunochemistry was performed with the APAAP method and enzyme activity revealed by fast red staining (Dako A/S, Glostrup, Denmark) [26]. Measurements were performed on APAAP stained bone marrow.…”
Section: Alkaline Phosphatase Anti-alkaline Phosphatase (Apaap)mentioning
confidence: 99%